Implicit stage topics - Karen Lahousse (Discours)
It has often been proposed that sentence-initial spatio-temporal elements specify the frame in which the whole proposition takes place and are topical (i.e. thematic). Whereas considerable attention has been paid to explicit spatio-temporal topics, Erteschik-Shir (1997, 1999) argues that spatio-temporal topics, or stage topics, can also be implicit.In this article we provide evidence in favour of the notion of implicit stage topic. We show that a certain number of nominal inversion cases in French, a syntactic configuration which is triggered by the presence of an explicit stage topic, are explained by the presence of an implicit stage topic. The fact that implicit stage topics interact with syntactic structure the same way explicit stage topics do constitutes a strong empirical argument in favour of their existence.